Penerapan Pembelajaran Tematik Di Kelas III SDN 058/II Sari Mulya Kecamatan Jujuhan Ilir Kabupaten Bungo - Agus Saputra; Muhammad Subhan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2021)
This research is motivated by a change in curriculum that is KTSP to curriculum 2013. This study aims to describe how the application of thematic learning in class III SDN 058/II Sari Mulya District Jujuhan Ilir Bungo District, starting from planning, implementation and assessment. This type of researchused in this study is qualitative research, the data generated is descriptive data. Data collection techniques used in this study include semistructured interviews and documentation. The nstrument used is in the form of an interview guide. Before the research the instrument is validated first by the validator. Based on these categories, the instruments developed can be used as research instruments. Research results show that (1) learning planning such as syllabus and lesson plans made by class III teachers have referred to syllabus indicators and lesson plans contained in Permendikbud No. 65 of 2013 concerning process standards. (2) the implementation of the learning process also uses a scientific approach. (3) learning assessment also uses authentic assessment. In general the application of learning carried out by class III teachers has referred to the RPP that has been designed in accordance with Permendikbud No. 65 of 2013 concerning process standards